2018
DOI: 10.1200/jop.18.00204
|View full text |Cite
|
Sign up to set email alerts
|

Managing Patients With Relapsed Small-Cell Lung Cancer

Abstract: Despite high response rates to initial therapy, relapses are common in patients with small-cell lung cancer (SCLC). Systemic therapy after first-line failure remains important in the treatment paradigm of SCLC. Reinitiation of a previously administered first-line chemotherapy regimen is recommended for relapse > 6 months from completion of initial therapy. For relapse ≤ 6 months of initial therapy, sequential therapy with single agents is recommended. Clinical trial enrollment should be considered at all stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The importance of surgery in the treatment early-stage SCLC has been widely acknowledged (19, 21, 22). And for SCLC patients at relatively advanced limited-stage, concurrent chemo-radiotherapy is greatly recommended (23, 24). Recent advances in radiology have enabled the early diagnosis of SCLC, and have prompted us to re-evaluate the effectiveness of surgery in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of surgery in the treatment early-stage SCLC has been widely acknowledged (19, 21, 22). And for SCLC patients at relatively advanced limited-stage, concurrent chemo-radiotherapy is greatly recommended (23, 24). Recent advances in radiology have enabled the early diagnosis of SCLC, and have prompted us to re-evaluate the effectiveness of surgery in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative is the combination CAV: cyclophosphamide-doxorubicin-vincristine (II, B). Other agents commonly used based on phase 2 trials are irinotecan, taxanes, gemcitabine, vinorelbine, or temozolomide [32]. Only around 20% of SCLC patients will receive the third-line therapy with modest results.…”
Section: Systemic Regimens For Es-sclc First Linementioning
confidence: 99%
“…SCLC remains a deadly disease, even as early as possible in the discovery and improvement of treatment options [18]. This study found that serum OPN levels in patients with SCLC were higher than in healthy controls.…”
Section: Discussionmentioning
confidence: 66%